Optimizing Green Investment and CSR to Enhance Palm Oil Firm Performance in Indonesia: The Role of Financial Slack as a Moderating Factor - Rafli, Muhammad Raihan; Juniar, Asrid; Salsabila, Nasywa Ghaida (Yayasan Sinergi Kawula Muda, 2025)
This study explores how green investment (GI) and corporate social responsibility (CSR) influence the performance of palm oil companies in Indonesia, with financial slack examined as a moderating factor. The research is motivated by the urgent need to address greenhouse gas emissions resulting from land conversion in palm oil plantations and the limited empirical studies focused on the agribusiness sector, particularly palm oil. Using a quantitative approach, the study analyzes data from eight palm oil sub-sector firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, generating 24 firm-year observations. Data were obtained from annual and sustainability reports, and analyzed using structural equation modeling with Partial Least Squares (SEM-PLS) via Warp-PLS 8.0. The results reveal that green investment has a significant negative impact on firm performance, while corporate social responsibility exerts a positive effect. Financial slack does not moderate the relationship between GI and performance but weakens the positive influence of CSR on performance. These findings suggest that the effectiveness of GI and CSR strategies in enhancing firm performance is contingent upon the firm’s financial condition. Moreover, in capital-intensive industries like palm oil, financial slack may complicate the intended benefits of CSR. The study’s limitations, particularly the small sample size and focus on listed companies, highlight the need for broader future research.